Leading the unleadable : how to manage mavericks, cynics, divas and other difficult people - Willett, Alan (AMACOM, 2017)
Difficult people are the worst part of a manager's job. Willett teaches you a straight forward process that gently, yet effectively, improves behaviors by revealing a core truth: most people actually want to contribute results, not cause headaches. What sets great managers apart is how they turn their problem players into productive team players.